Socialization about Determining Technical Specifications for Procurement of Goods and Services in Payung Village - Mei Brilian Harefa; Dasrizal; Sufrial Hendri; Alif Saum Rizalitaher; Nobertus Giawa; Mhd Diky Yusnanta Tarigan (PT FORMOSA CENDEKIA GLOBAL, 2023)
Government Decentralization or Regional Autonomy is a form of Central Government to Regional Governments to carry out good and systemic governance. Irregularities in the procurement system also opened up opportunities for corruption, resulting in many protests and suspicions about the integrity of the procurement process. Many village officials still do not understand the procedures for managing village funds, making these village funds less well-targeted and their utilization less than optimally received by the community. That is the reason for the importance of socializing the procurement of goods and services, especially regarding technical specifications to village officials. With this socialization, it is hoped that the community and village officials will have an understanding and knowledge of the preparation of technical specifications for the procurement of goods and services. Thus, in the future, the community and Umbrella Village officials will be able to maximize the village budget properly, efficiently, and on target.